2023
DOI: 10.1002/csr.2624
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about ESG and risk? A systematic and bibliometric review

Maria Elena De Giuli,
Daniele Grechi,
Alessandra Tanda

Abstract: Environmental, Social and Governance (ESG) issues have become particularly relevant in the agendas of policymakers, investment decisions by companies and asset allocation process of investors. However, the transition to a greener and more sustainable economic system is not without risks. The literature has investigated the relationship between ESG and risk in different ways, through multiple perspectives and approaches. We select all documents with “ESG” and “Risk” in the title, abstracts and keywords availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…This observation aligns with the conclusions drawn in studies such as those mentioned by Cohen (2023) and Gupta et al (2021), which emphasize the impact of ESG factors on financial performance. Furthermore, the results of Hypothesis 3 revealed a significant difference in returns attributable to ESG considerations, aligning with the research by Stiadi (2023) and De Giuli et al (2024), which emphasizes the importance of considering ESG factors in investment decision-making processes. Lastly, Hypothesis 4 explored the presence of a weak negative correlation between certain ESG factors and investment returns, which was supported by the presence of a positive annualized alpha of 4.37%.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This observation aligns with the conclusions drawn in studies such as those mentioned by Cohen (2023) and Gupta et al (2021), which emphasize the impact of ESG factors on financial performance. Furthermore, the results of Hypothesis 3 revealed a significant difference in returns attributable to ESG considerations, aligning with the research by Stiadi (2023) and De Giuli et al (2024), which emphasizes the importance of considering ESG factors in investment decision-making processes. Lastly, Hypothesis 4 explored the presence of a weak negative correlation between certain ESG factors and investment returns, which was supported by the presence of a positive annualized alpha of 4.37%.…”
Section: Discussionsupporting
confidence: 85%
“…Bibliometric Review of Environmental, Social, andGovernance Factors andRisk De Giuli et al (2024) conduct a bibliometric review, analyzing literature on ESG factors and risk, identifying trends and key research areas. Their study underscores the critical role of finance in promoting sustainable growth and emphasizes the need for further research in understanding ESG risks and their implications for financial markets (De Giuli et al 2024).…”
Section: Predictive Analysis Using Social Media Sentimentsmentioning
confidence: 98%
“…Selection of all documents with "ESG" and "Risk" in the title, abstracts and keywords available in Scopus and, after removing nonrelevant papers, we are left with a sample of 589 documents published in the period 1983-2022, provided a view of the most important studies. The results show that over time, ESG has gained increasing attention from the literature, but a clear taxonomy of ESG risks appears to be missing [48]. The main conclusions concern the usage of keywords related to sustainability and the evolution from "social responsibility" to a more comprehensive term, such as "ESG".…”
Section: Mcdonald'smentioning
confidence: 98%
“…The main conclusions concern the usage of keywords related to sustainability and the evolution from "social responsibility" to a more comprehensive term, such as "ESG". The research [48] identified several key challenges that companies face when attempting to integrate ESG factors into their decision-making processes, which include a lack of standardized ESG data and metrics, difficulties in identifying material ESG issues, and the need for greater transparency and accountability in ESG reporting. Additionally, the core stream of research investigates the problems of asset managers and companies in terms of how to improve economic or financial metrics through ESG investing.…”
Section: Mcdonald'smentioning
confidence: 99%
“…Previous research has examined the relationship between risk and firm performance (Çamlibel et al, 2021;Soares da Fonseca, 2020), as well as the potential impact of ERM on firm performance (Arnold et al, 2015;Farrell & Gallagher, 2015). Prior studies have also explored the relationship between risk and CSR (Bouslah et al, 2018;Cupriak et al, 2020;De Giuli et al, 2024;Hummel et al, 2021) and the relationship between ERM and CSR and its impact on performance (Chairani & Siregar, 2021;Naseem et al, 2020). However, a more thorough understanding of these relationships is necessary, especially in terms of ERM implementation and its alignment with a company's strategic dimensions, particularly CSR.…”
mentioning
confidence: 99%